2021
DOI: 10.1177/21582440211046589
|View full text |Cite
|
Sign up to set email alerts
|

Asymmetric Impact of FDI and Exchange Rate on Tourism: Evidence From Panel Linear and Nonlinear ARDL Model

Abstract: This study analyzes the long run as well as short run linear and nonlinear impact of foreign direct investment (FDI) and exchange rate on tourism in South Asian countries. The study uses annual panel data of five South Asian countries that is Bangladesh, India, Nepal, Pakistan, and Sri Lanka from 1995 to 2019 and applies panel linear autoregressive distributive lag (ARDL) and nonlinear autoregressive distributive lag (NARDL) methodology to analyze the long run and short run relationship among the variables. Re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
6
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(10 citation statements)
references
References 37 publications
1
6
0
Order By: Relevance
“…A study by Belloumi [45], examined tourism receipts and exchange rate nexus in Tunisia and concluded that there is a cointegrating relationship between tourism and economic growth. An increase in foreign direct investment (FDI) and appreciation of the exchange rate contracts the tourism demand of the country while in the long-run the depreciation of domestic currency and decrease in FDI inflow results in more tourist inflow [41]. Similar findings were obtained by [46] and [47] where they revealed that reduction in FDI inflow and depreciation of foreign exchange rate results in positive tourism development.…”
Section: Tourism and Exchange Ratesupporting
confidence: 65%
See 1 more Smart Citation
“…A study by Belloumi [45], examined tourism receipts and exchange rate nexus in Tunisia and concluded that there is a cointegrating relationship between tourism and economic growth. An increase in foreign direct investment (FDI) and appreciation of the exchange rate contracts the tourism demand of the country while in the long-run the depreciation of domestic currency and decrease in FDI inflow results in more tourist inflow [41]. Similar findings were obtained by [46] and [47] where they revealed that reduction in FDI inflow and depreciation of foreign exchange rate results in positive tourism development.…”
Section: Tourism and Exchange Ratesupporting
confidence: 65%
“…The real and nominal appreciation of the currency leads to a negative impact on the tourism development in the country [40]. Exchange rate has PLOS ONE asymmetric impact on tourism on tourism development in developing countries such as, India, Bangladesh, Pakistan and Nepal in the short run [41]. Boskurt et al [42] applied dynamic common correlated effects (DCCE) approach in their study on demand and exchange rate shocks on tourism development and concluded that effects of the exchange rate shocks are temporary on the tourism development.…”
Section: Tourism and Exchange Ratementioning
confidence: 99%
“…The results revealed that the exchange rate impacts both economic growth as well as tourism in the selected islands. Similarly, Munir and Iftikhar ( 2021 ) also explored the tourism, foreign direct investment, and exchange rate relationship in different South Asian countries. The data of Bangladesh, India, Nepal, and Sri Lanka as well as Pakistan from 1995 to 2019 was tested by employing ARDL and NARDL approaches.…”
Section: Literature Reviewmentioning
confidence: 99%
“…H 2 Pass-through of monetary policy to restaurant and hotel prices is asymmetric in the US Munir and Iftikhar (2021), Irandoust (2019), and Ongan et al (2018) have examined an empirical connection between exchange rates and tourism and recreation activities. For instance, Munir and Iftikhar (2021), while employing a hidden cointegration analysis within a likelihood-based panel framework for 10 European countries, examined the asymmetric effect of exchange rate on tourism demand.…”
Section: Monetary Policy and Restaurant-hotel Pricesmentioning
confidence: 99%
“…H 2 Pass-through of monetary policy to restaurant and hotel prices is asymmetric in the US Munir and Iftikhar (2021), Irandoust (2019), and Ongan et al (2018) have examined an empirical connection between exchange rates and tourism and recreation activities. For instance, Munir and Iftikhar (2021), while employing a hidden cointegration analysis within a likelihood-based panel framework for 10 European countries, examined the asymmetric effect of exchange rate on tourism demand. The investigation affirmed that tourism demand responds asymmetrically to the exchange rate fluctuations especially in the long run, further suggesting that depreciation and appreciation of exchange rates affect tourism demand in different dimensions.…”
Section: Monetary Policy and Restaurant-hotel Pricesmentioning
confidence: 99%